National survey of the management of eye emergencies in the accident and emergency departments by senior house officers: 10 years on—has anything changed?. (22nd January 2008) - Sim, D; Hussain, A; Tebbal, A; Daly, S; Pringle, E; Ionides, A
Abstract : Objective: To assess changes in basic ophthalmic training of accident and emergency (A&E) senior house officers (SHOs) in the last 10 years, their own perceived level of confidence and the availability of appropriate equipment in their departments. Methods: A standardised structured questionnaire from a telephone survey carried out in 1993 was used. One SHO from each A&E department listed in the British Association of Emergency Medicine directory of 2003 was chosen at random and interviewed. Results: 168 A&E departments were contacted and 133 SHOs were successfully interviewed (response rate 79.2%). The number of A&E departments with a slit lamp increased by 25.7% from 1993, and slit lamp training increased by 21%. There was no significant change in the prevalence of training in the management of eye emergencies (74.0% in 1993 vs 77.4% in 2003) and the proportion of SHOs who felt confident in dealing with these cases was unchanged. Conclusions: A&E departments are better equipped with slit lamps 10 years on, and staff are being trained to use them. This has unfortunately not improved the confidence levels in dealing with eye emergencies, reflecting the lack of adequate basic ophthalmic training for A&E SHOs. Recent changes in postgraduate medical training could provide a platform to bring about the changes required.